2019
DOI: 10.33265/polar.v38.3366
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics and persistence of rabies in the Arctic

Abstract: Rabies is a major issue for human and animal health in the Arctic, yet little is known about its epidemiology. In particular, there is an ongoing debate regarding how Arctic rabies persists in its primary reservoir host, the Arctic fox (Vulpes lagopus), which exists in the ecosystem at very low population densities. To shed light on the mechanisms of rabies persistence in the Arctic, we built a susceptible–exposed–infectious–recovered (SEIR) epidemiological model of rabies virus transmission in an Arctic fox p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 47 publications
0
20
0
Order By: Relevance
“…The genetic diversity of the Arctic lineage of rabies virus described here clearly supports a model in which the virus is continuously evolving through mostly neutral mutation and purifying selection to spawn distinct genetic groups. Modelling studies of Arctic rabies have suggested that a variety of factors including high transmission rates, relatively short incubation periods but long infectious periods and ongoing immigration of infectious conspecifics from other areas could help in maintaining rabies outbreaks in northern Canada; however, various scenarios in which outbreak die-offs occurred were also often predicted [ 60 ]. Indeed, the rabies virus phylogeny illustrated here does suggest that while some viral groups appear to circulate only very locally and die off relatively quickly (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…The genetic diversity of the Arctic lineage of rabies virus described here clearly supports a model in which the virus is continuously evolving through mostly neutral mutation and purifying selection to spawn distinct genetic groups. Modelling studies of Arctic rabies have suggested that a variety of factors including high transmission rates, relatively short incubation periods but long infectious periods and ongoing immigration of infectious conspecifics from other areas could help in maintaining rabies outbreaks in northern Canada; however, various scenarios in which outbreak die-offs occurred were also often predicted [ 60 ]. Indeed, the rabies virus phylogeny illustrated here does suggest that while some viral groups appear to circulate only very locally and die off relatively quickly (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Parameter values provided in Table 1 are based on Anderson et al (1981) and Simon et al (2019), and parameter values were also cross-referenced with Mørk and Prestrud (2004) to ensure biological relevance for arctic fox populations. The parameter set, derived from demographic studies of foxes, yields a theoretically simulated disease density threshold of 1 fox/km 2 .…”
Section: Two-patch Modelmentioning
confidence: 99%
“…However, those commonly used models can predict densities not found in nature. For instance, Anderson et al (1981) predicts rabies persistence in Europe when densities of its regional host, red fox (Vulpes vulpes), are as low as 1 fox/km 2 , yet rabies persists in the tundra when densities of arctic fox (Vulpes lagopus) are well below this threshold (Simon et al 2019). One way such a contradiction could exist is that environmental heterogeneity may lower threshold host densities for disease persistence.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations